Slobodan Prosperov Novak, tko je to? Ili: O pozadini jednog projekta kanonizacije književne povijesti - Rafolt, Leo (Array, 2004)
In this article author argues the concept of literary canon and also the concept of literary history in the postmodern society. Analyzing Novak's syntetic work of literary history, his History of Croatian Literature, article trys to encompass metodological problems of historical writing and literary promotion as such.